Design of a novel plasmonic nanoconjugated analytical tool for ultrasensitive antigen quantification - Fraire, Juan Carlos (2016)
To date, while various diagnostic approaches for antigen detection have been proposed, most are too expensive, lengthy and limited in sensitivity for clinical use. Nanoparticle systems with unique material properties, however, circumvent these problems and offer improved accuracy and sensitivity over current methods like the enzyme-linked immunosorbent assay (ELISA). Herein, we present a novel functionalization strategy of plasmonic nanoparticle probes capable of specific quantification of antigens directly in clinical samples. A nanoconjugation strategy that allows one to perform an intensity depletion immuno-linked assay (IDILA), involving specific antibodies that target the antigen of interest was designed to obtain a calibration curve and achieve the quantification of the antigen in clinical samples in the same experiment using a microplate reader (i.e., an UV-vis spectrophotometer). Finally, the IDILA methodology allowed specific detection of various clinically relevant antigens, with significantly improved sensitivity over the ELISA. Furthermore, the assay was shown to be robust, reliable, cheap and rapid, diagnosing antigens in clinical serum samples within 2 hours.